Moral disengagement in manufacturing : a Malaysian study of antecedents and outcomes - Saidon, Intan Marzita (Curtin University, 2012)
The premise of this research is that in a normal situation people may not involve in any inhumane, unethical conduct unless they can successfully justify to themselves the rightness of their action. According to social cognitive theory, individual behaviour could be explained through a self-regulatory system. Individuals are believed to have control over their own thoughts and behaviour through the self-regulatory processes. However, an individual’s self-regulatory system will only operate if it is activated because this system can be activated and deactivated selectively. Moral disengagement is a construct that explains possible keys to deactivation of an individual’s self-regulatory system. Once the system is deactivated, an individual will be freed from psychological feelings of discomfort in performing unethical behaviour.Applying social cognitive theory and supported by social exchange and transformational leadership theories, this research attempts to investigate the antecedents and outcomes of moral disengagement of employees in large manufacturing companies in Malaysia. Although much has been done to investigate various outcomes of moral disengagement, none has related moral disengagement to workplace deviance. Further, little is known about the antecedents of moral disengagement. On top of that, this research incorporates transformational leadership style as a variable, which possibly constrains the likelihood that moral disengagement leads to workplace deviance.A two-stage sampling technique was applied to randomly collect data from 669 employees in large electrical and electronic manufacturing companies in Malaysia. A structural equation modelling software (Analysis of Moment Structures or AMOS) was applied to examine the direct and mediating effects hypotheses. Hierarchical regression was used to test the moderating hypotheses. AMOS, a more recent approach in analysing moderating effects was applied as an alternative analysis and to further extend the body of knowledge.Results failed to support hypothesized relationships between the two personality traits (extraversion and conscientiousness) and moral disengagement. Only organisational ethical climate was confirmed to have a significant negative relationship with moral disengagement. Moral disengagement was also found to partially mediate the relationships between organisational ethical climate and interpersonal as well as organisational deviance. Findings confirmed that moral disengagement is associated with both types of deviance. In addition, transformational leadership style was found to moderate the relationship between moral disengagement and interpersonal deviance. Also, interpersonal deviance was found to be associated with organisational deviance.This research makes several theoretical contributions and provides further insights on the antecedents and outcomes of moral disengagement particularly in Malaysia, a country categorised as having a high degree of power distance and collectivism. Methodological and practical implications were discussed and several potential avenues for future research were identified and proposed. In short, this research helped to produce a segment in a more inclusive global picture of the antecedents and outcomes of moral disengagement.